EUROPEAN SUPREME AUDIT INSTITUTIONS: THE CONSTITUTIONAL AND LEGAL COORDINATES OF DIAGONAL PUBLIC ACCOUNTABILITY - SANDA MIHAI-RĂZVAN; MILITARU ELIAN-GABRIEL (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2023)
Supreme audit institutions (SAIs) have recently undergone major paradigm shifts regarding their role and purpose in the public framework, starting from simple guardians of public finances to becoming a provider of consultancy and foresight for the optimization of public mechanisms and policies. However, the current trend stems from their own preoccupation for social accountability and relevance, while their legal framework lags behind, often antiquated in design and approach. Furthermore, the diversity in SAIs’ mandates, organizational models and relation to legislature, coupled with somewhat overlapping SAI theoretical models, led us to perform an in-depth research on the constitutional and legal framework of EU member states’ SAIs, in order to better bring to light their constitutional or parliamentary origins, the relation to governments and parliaments and their governance typology. The research contributes by adding clarity to a less-researched field – that of supreme audit institutions and their legal foundation. To our best knowledge, this is the first EU-wide comparative study of the constitutional al legal framework that underpins the member states’ SAIs and its results help better classify some of the European SAIs, even changing some of their governing models from their own description.